Effect of Rythmol (propafenone HCl) administration during pregnancy in Wistar rats. Issue 8 (2nd May 2022) - Abd‐Allah, Entsar R.; Amin, Salma; El Ghareeb, Abd El Wahab; Badawy, Mohamed A.
Abstract: Propafenone is a well‐known Class 1C antiarrhythmic agent that has sodium channel blocking properties as well as the ability to block 13 other channels and a modest calcium antagonistic effect. Propafenone has a profound electrophysiologic effect on auxiliary atrioventricular circuits and in patients with atrioventricular nodal reentry tachycardia can obstruct conduction in the fast conducting pathway. Furthermore, propafenone is less likely than other Class 1C drugs to cause proarrhythmia. However, although this medicine can pass through the placenta, the effects during pregnancy remain unknown. Here, we investigated the potential teratogenic and genotoxic effects of Rythmol during rat development. Pregnant Wistar rats received 46.25 mg/kg body weight of propafenone daily by gavage from Gestation Day (GD) 5 to GD 19. At GD 20, the dams were dissected, and their fetuses were assessed via morphologic, skeletal, and histologic investigation. In addition, a comet assay was used to measure DNA impairment of fetal skull osteocytes and hepatic cells. The study showed that propafenone treatment of pregnant rats led to a marked decrease in gravid uterine weight, number of implants/litter, number of viable fetuses, and bodyweight of fetuses but a clear increase in placental weight and placental index in the treated group. Frequent morphologic abnormalities and severe ossification deficiency in the cranium bones were observed in the treatment group. Various histopathological changes were observed in the liver, kidney, and brain tissues of maternally treated fetuses. Similarly, propafenone induced DNA damage to examined samples. Thus, our study indicates that propafenone may be embryotoxic in humans.